Shortening and extrusion in the East Anatolian Plateau: how was Neogene Arabia-Eurasia convergence tectonically accommodated? - Hinsbergen, Douwe J. J. van; Gürer, Derya; Koç, Ayten; Lom, Nalan (Earth and planetary science letters, 2024)
Deformation in orogenic belts is typically widely distributed but may be localized to form discrete, fast-moving fault zones enclosing semi-rigid microplates. An example is the Anatolian microplate, which is extruding westwards from the East Anatolian Plateau in the Arabia-Eurasia collision zone along the North and East Anatolian Faults that cause devastating earthquakes, including those of February 6, 2023 in Southeast Anatolia. Here, we summarize the orogenic architecture of the East Anatolian Plateau and its underlying kinematic history since the Cretaceous, and use this to reconstruct the tectonic situation that existed at the onset of and during the development of the Neogene East Anatolian Plateau and the Anatolian microplate. The orogen first formed in the late Cretaceous by subduction-accretion of microcontinental lithosphere below Neotethys oceanic lithosphere. Then, in Paleogene time, the accretionary orogen underwent regional upper plate extension, causing crystalline crust exhumation and deep-marine basin formation. From early Miocene time onwards, the extended orogen shortened again and must have accommodated ∼350 km of convergence, making crust up to 45 km thick, and causing >2 km of uplift. Since the ∼13 Ma onset of North Anatolian Fault formation, microplate extrusion absorbed no more than 25 % (∼65 km) of Arabia-Eurasia convergence and even during this time alone, >200 km of convergence must have been accommodated by continued ∼N-S shortening. We highlight the need for field studies of the East Anatolian Plateau to identify where and how this major shortening was accommodated, what role it played in plateau rise and the onset and dynamics of microplate extrusion, and to better assess seismic hazards.
This is a non-peer reviewed manuscript, submitted for publication in Earth and Planetary Science Letters
Gesehen am 13.01.2025
Online verfügbar 14 June 2024, Version des Artikels 14 June 2024